Energy Efficient Secure Communication Model against Cooperative Eavesdropper - Radzharam A. kumar Akash; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Ruy D. Dinis; Beko M. Marko (2021, 2021)
Title screen